The Marketing of Postcolonial Literature - Mendes, Ana Cristina (2017)
This chapter focuses on the commercial dynamics of contemporary literary culture as they play out in recent South Asian fiction written in English by cosmopolitan authors. The focus of my analysis rests on literary texts which have emerged as sites where experiences, desires, transitions and anxieties related to the profound social and structural changes that are shaping the socio-economic landscape of the world are drawn on and negotiated. The main argument of this chapter is that, even though these narratives of (dis)possession problematize problematise capitalism’s logics of asymmetrical distribution of power and wealth, the high profile of their authors within the global circuits of production and reception of postcolonial texts is generated by the same logics. In fact, the ways these narratives are made to circulate within the global market at times counteract the expressed agenda of their authors. Altogether, I will approach recent South Asian fiction as a current central paradigm of postcolonial literature marketing, one that can be applied to other contexts. For instance, this paradigm resonates with the appropriation by British publishers of the process of canon-formation of postcolonial Anglophone African writing since the 1960s (cf. Davis 2013). Before elaborating on recent economic and social developments in South Asia and their repercussions in fiction contemporaneous with them, I will therefore develop a conceptual perspective on postcolonial literature marketing, mainly using ideas from the methodology of the ‘new sociology of literature.’